The effectiveness of muslimah fashion towards teenagers behavior / Siti Norizan Bakar - Bakar, Siti Norizan (Faculty of Art and Design, 2014)
The developments of fashion industry create moments and sparks colors on this world. ~t created scenes and recalled many memories. The fashion industry had started in a very long time ago and seems to be more important in people's lifestyle. The rise of the Muslimah Fashion that was realized today shocked many people. As many know, the fashion industry was monopolized by the western fashions for a long period of time however, the trend and style brought by many local and international Muslimah fashionista, seems to bring changes to the fashion world on this era. The design and style of Muslimah Fashion that focused on covering most part of the body and show modesty appears to save the women.